Unexpected readings: looking for beauty in books at the Veneto Institute of Oncology. - Prevedello, Giuliana; Bozzato, Valentina; Gnoato, Marianna (Journal of EAHIL, 2022)
Hospices are specialized facilities for palliative care. With the purpose of improving the quality of life and making the Veneto Institute of Oncology (IOV) a more reassuring and less impersonal place, the Scientific Library has designed a project called Letture inattese (Unexpected Readings) that brings books to guests, carers and the health workforce of the Hospice. With people in mind, rather than their illness, this project aims to generate a moment of wonderment, relief and recreation through the beauty that can be found in books. This first non-scientific patients’ library at IOV intends to create opportunities for deepening the quality of human relationships between the patients, their families and the healthcare professionals.